Assessment of chronic benign and cancer pain using blood plasma biomarkers - Rokyta, Richard; Haklova, Olga; Yamamotova, Anna (Neuro endocrinology letters, 2009)
OBJECTIVE: The objective was a systematic study of the biochemical markers which are descriptive for the dynamics of pain processes. MATERIALS AND METHODS: The patients who had not been systematically treated for pain prior to their participation in this study consisted of 20 non-oncological (mean age 56.5 years) and 20 oncological patients (mean age 64.8 years). Pain intensity, assessed using the visual analogue scale (VAS) on a scale from 0-10, and the following biochemical parameters were measured during the initial patient workups: blood serum total protein, glucose, total cholesterol, HDL cholesterol, LDL cholesterol, atherosclerotic indexes, triacylglyceroles, apolipoprotein A, apolipoprotein B, albumin, alpha1 globulin, alpha2 globulin, beta globulin and gamma globulin. Biochemical measurements were repeated as soon as VAS assessments fell below 5. Therapy in non-oncological patients involved administration of NSA and weak opioids; while oncological patients received NSA, medium strength and strong opioids, and antidepressants. RESULTS: Prior to therapy, concentration of albumin in serum, HDL cholesterol, and apolipoprotein A were lower, whereas CRP and alpha1 globulin were higher in oncological patients compared to non-oncological patients. After therapy, levels of glucose and alpha1 globulin were significantly higher and levels of apolipoprotein A were lower in oncological patients compared to non-oncological patients. Irrespective of diagnosis, patients treated with antidepressants showed higher levels of gamma globulin compared to non treated patients. CONCLUSIONS: We can conclude that observed biochemical markers in patients with malignancies are more similar to the values of patients with chronic benign pain than to the values of patients with acute pain.
Keywords: dospělí; Female; biologické markery; Biomarkers; Adult; ženské pohlaví; Neoplasms; nádory; lidé; bolest; Male; Aged; Pain; chronická nemoc; lidé středního věku; senioři; mužské pohlaví; Chronic Disease; Middle Aged; Humans